The Development of Creative Problem Solving Ability Using Design Thinking with Visual Thinking Techniques in the S22101 Social Studies of Grade 8 Students at Satri Rachinuthit School - Appakarat, Chaninat; Chumsukon, Montha (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to develop students’ creative problem-solving ability and learning achievement through the integration of the Design Thinking process with Visual Thinking techniques in Social Studies course code S22101. The target group consisted of 36 Mathayomsuksa 2/1 students at Satri Rachinuthit School in the first semester of the 2024 academic year, selected by purposive sampling. The study employed an action research design. The research instruments included: (1) six lesson plans using the Design Thinking process combined with Visual Thinking techniques (12 periods); (2) data collection tools, namely learning activity record forms, classroom observation forms, student interviews, a creative problem-solving test, and formative tests; and (3) evaluation tools, including a creative problem-solving assessment and an achievement test. Data were analyzed using descriptive statistics, including mean, standard deviation, and percentage. The findings revealed that 29 students (80.55%) passed the criteria for creative problem-solving ability with an average score of 47.97 (79.95%), which was higher than the specified benchmark. Furthermore, 31 students (86.11%) passed the learning achievement criteria with an average score of 24.72 (82.41%), also exceeding the benchmark. These results indicate that the integration of the Design Thinking process with Visual Thinking techniques effectively enhanced students’ creative problem-solving ability and learning achievement.